UMP shares research works and expertise in IT with 4 foreign IHL - UMP, PNC
For the first time Universiti Malaysia Pahang (UMP) joined forces with four foreign institutes of higher learning (IHL) to organise an International conference on computer science and information technology (ICoCSIM) at Niagara Hotel, Lake Toba, Parapat, North Sumatera in Indonesia on December 5, 2012.